Upaya Meningkatkan Pemahaman Nilai Moral Agama Melalui Metode Bercerita Pada Anak Usia 5-6 Tahun Di TK Pembina 02 Rumbio Jaya - Della Safitri; Yenda Puspita; Nurmalina Nurmalina (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research is motivated by the low understanding of moral values ​​in group B children of Pembina 02 Rumbio Jaya Kindergarten, Simpang Petai Village, Rumbio Jaya District, Kampar Regency. The solution to this problem is by implementing the storytelling method. This study aims to determine whether the storytelling method can improve understanding in children at Pembina 02 Rumbio Jaya Kindergarten. The subjects in this study consisted of 15 children, 8 girls and 7 boys, the method used in this study was the Classroom Action Research (CAR) method. This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings, each meeting consisted of the following activities: Planning, Acting, Observing and Reflecting. Data collection techniques were carried out through observation and documentation, the results of the study showed that there was an increase in children's understanding of moral values ​​in each of the child's indicators, starting from the pre-action, most children were still in the "not yet developed" category, but after the actions of cycles I and II, there was a significant increase in indicators such as answering questions, imitating scenes, drawing or making artwork, showing fair and disciplined actions, and expressing opinions. Storytelling activities have been proven effective in providing fun and meaningful stimulation for children's understanding. Thus, this activity can be used as an alternative innovative learning method for early childhood